Comparison of enrichment methods for efficient nitrogen fixation on a biocathode - Rous, Axel; Santa-Catalina, Gaëlle; Desmond-Le Quémener, Elie; Trably, Eric; Bernet, Nicolas (Peer Community Journal, 2024)

(untitled)
The production of nitrogen fertilizers in modern agriculture is mostly based on the Haber-Bosch process, representing nearly 2% of the total energy consumed in the world. Low-energy bioelectrochemical fixation of N2 to microbial biomass was previously observed but the mechanisms of microbial interactions in N2-fixing electroactive biofilms are still poorly understood. The present study aims to develop a new method of enrichment of autotrophic and diazotrophic bacteria from soil samples with a better electron source availability than using H2 alone. The enrichment method was based on a multi-stage procedure. The first enrichment step was specifically designed for the selection of N2-fixing bacteria from soil samples with organic C as electron and carbon source. Then, a polarized cathode was used for the enrichment of autotrophic bacteria using H2 (hydrogenotrophic) or the cathode as electron source. This enrichment was compared with an enrichment culture of pure diazotrophic hydrogenotrophic bacteria without the use of a microbial electrochemical system. Interestingly, both methods showed comparable results for N2 fixation rates at day 340 of the enrichment with an estimated average of approximately 0.2 mgNfixed/L.d. Current densities up to -15 A/m² were observed in the polarized cathode enrichments and a significant increase of the microbial biomass on the cathode was shown between 132 and 214 days of enrichment.These results confirmed an enrichment in autotrophic and diazotrophic bacteria on the polarized cathode. It was hypothesied that autotrophic bacteria were able to use either the H2 produced at the cathode or directly the cathode through direct electron transfer (DET) as more biomass was produced than with H2 alone. Finally, the analysis of the enriched communities suggested that Desulforamulus ruminis mediated microbial interactions between autotrophic anaerobic and heterotrophic aerobic bacteria in polarized cathode enrichment. These interactions could play a key role in the development of biomass in these systems and on N2 fixation. Based on these findings, a conceptual model on the functioning of mixed cultures N2-fixing electroactive biofilms was proposed.